Build back better: What is it, and what should it be? - Ilan Noy; Benno Ferrarini; Donghyun Park (Asian Development Bank (ADB), 2019)
The long-term economic consequences of catastrophic disasters are poorly understood. This lacuna is surprising since the long-term effects may be much more important than the short-term emergency phase. In contrast, the policy literature is full of aspirational plans to "build back better" (BBB) - a recovery that leads to improvements above and beyond the predisaster status quo. BBB is clearly multidimensional, but the focus here is the assessment of economic BBB. We first delve into two wellknown BBB cases - Sri Lanka after the 2004 Indian Ocean tsunami and Sichuan province in the People's Republic of China after its 2008 earthquake. Following that analysis, the central objective of our paper is to propose a more precise and concrete definition of economic BBB. To do so, we propose four criteria against which one should evaluate BBB policies: safety, speed, fairness (inclusiveness), and socioeconomic potential. We conclude by describing each of the four criteria in greater detail.
Keywords: H54; Q54; 330; build back better; disaster; economic impact; long run; recovery